Economic and financial crisis in Portugal: Context, political responsibility, and media’s new challenges facing the threat of a possible new financial crisis. - Cunha, C.; Lobo (European Communication Research and Education Association (ECREA) Annual Conference, 2021)
The global economic and financial crisis from 2008 onwards, originating in the United States and triggered by the bankruptcy of the Lehman Brothers Bank, has had negative effects on a number of financial institutions worldwide, a process known as the subprime lending crisis. The repercussions for Europe became the sovereign debt crisis beginning in 2009, giving rise to the bailouts of Greece and Ireland in May and November 2010 and April 2011 in Portugal. Thus emerged the so-called Eurozone crisis in Europe. National and international politicians and institutions were blamed for the situation. The politicians positioned themselves in the face of the crisis and presented alternatives. Citizens also commented on who should take responsibility for the crisis. This analysis examines who is seen as responsible for the economic crisis in Portugal beginning in 2008 and ending in 2016 by focusing on the voters and politicians’ perspectives (electoral candidates and elected MPs). For context, economic development theory and Portuguese economic history from 1974 up to and through the crisis is presented. The methodology is based on data from our participation in Freire, A., Lisi, M. Tsatsanis, E., Viegas, J.M.L and Correia, A. (2018), “Merged Data: Portuguese Citizens, MPs and Candidate Surveys 2008-2018”, research project at CIES-IUL and IPRI-NOVA, “Crisis, Political Representation and Democratic Renewal: The Portuguese case in the Southern European context”, FCT: PTDC/IVC-CPO/3098/2014 to demonstrate how candidates and members of parliament’s views of the economic crisis compare to the general public´s.